Influence of homeopathic treatment with comfrey on bone density around titanium implants. A digital subtraction radiography study in rats - Sakakura, Celso Eduardo; Neto, Rubens Spin [UNESP]; Bellucci, Marina [UNESP]; Wenzel, Ann; Scaf, Gulnara [UNESP]; Marcantonio, Elcio [UNESP] (Wiley-Blackwell, 2008)
Objective: The objective of this study was to evaluate the influence of homeopathic treatment with comfrey (Shymphytum officinalis 6CH) on radiographic bone density and area around titanium implants.Material and methods: Forty-eight rats were divided into two groups of 24 animals each: a control group (C) and a test group (SO). Each animal received one titanium micro-implant placed in the tibia. The animals in Group SO were subjected to 10 drops of comfrey 6CH per day mixed into their drinking water until the day of sacrifice. Eight animals of each group were sacrificed at 7, 14 and 28 days post-surgery, respectively.Standardized digital radiographs were obtained on the day of implant installation (baseline images) and on the day of sacrifice (final images). Digital subtraction of the two corresponding images was performed to evaluate changes in bone density and the area related to change around the implant between baseline and final images.Results: Subtraction images demonstrated that a significant difference existed in mean shade of gray at 14 days post-surgery between Group SO (mean 175.3 +/- 14.4) and Group C (mean 146.2 +/- 5.2). Regarding the area in pixels corresponding to the bone gain in Group SO, the differences observed between the sacrifice periods and groups were only significant at 7 days sacrifice between Group SO (mean 171.2 +/- 21.9) and Group C (mean 64.5 +/- 60.4).Conclusion: Within the limits of this study, comfrey administration promotes an increase in radiographic bone density around titanium implants in the initial period of bone healing.
Keywords: bone density; comfrey; digital subtraction radiography; osseointegration; titanium implants